Measurement of CT Number Uniformity Value at Various X-ray Tube Current Settings in CT Scanning - Ni Nyoman Ratini; Gusti Ngurah Sutapa; Ni Kadek Nova Anggarani; I Gde Antha Kasmawan; Anastasia Jessing Gamalita Mberato (Postgraduate, University of Mataram, 2025)
Studies on the analysis of variations in CT number uniformity values for CT-Scan images has been conducted. This study aims to evaluate the image quality value by uses various tube currents (mAs) in Siemens merk water phantom irradiation to assess the value of image quality. A Siemens Somatom Scope CT-Scan with current variations of 180 mAs, 200 mAs, 220 mAs, 240 mAs, and 260 mAs was used. The image results were then anlyzed for quality through the CT number uniformity value test. Using a marker size of 12.56 cm2, the ROI method was applied at five different picture points: the center, 3, 6, 9, and 12 o'clock. For each current variation used in this study, 3 irradiation was carried out and 5 image slices were taken from each irradiation.This resulted of the analysis the CT number uniformity value was shown to be significantly reduced by the tube current strength (R2=0.9896, p-value<0.05), according to the research. The test showed that the uniformity CT number value decreased from 0.217 HU to 0.031 HU as the tube current strength was increased, bringing it closer to the reference value (0 HU). The consistency CT number values acquired in this study remain within the 2 HU tolerance limits established by BAPETEN.